Bioactivity and metabolite profile of papaya (Carica papaya) seed extract - MUHAMMAD ALFARABI; FORMAN ERWIN SIAGIAN; JAP MAI CING; TRINI SURYOWATI; TURHADI TURHADI; MICHELTHELIA SULIJAYA SUYONO; MONICA SYEFI FEBRIYANTI; FITRI BORU NAIBAHO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Alfarabi M, Siagian FE, Cing JM, Suryowati T, Turhadi, Suyono MS, Febriyamti MS, Naibaho FB. 2022. Bioactivity and metabolite profile of papaya (Carica papaya) seed extract. Biodiversitas 23: 4589-4600. Papaya (Carica papaya) seeds are part of the papaya plant which is a source of organic waste. However, there are many scientific studies thatstate the metabolites found in papaya seeds have various benefits in medical aspects. Accordingly, the objective of this study was to examine the antioxidant and cytotoxic activity of California and Bangkok type papaya seeds which are two local papaya types and widely consumed by the people of Indonesia. These papaya seeds'metabolite profiling was also conducted in this study therefore the antioxidant activity and cytotoxic mechanisms can be estimated. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) method is used to investigate the antioxidant activity while 3- (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) isused to investigate the cytotoxic effect of extract. Metabolites contained in papaya seeds were measured by Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography-Mass Spectrometry-QTOF (LC-MS/MS-QTOF). The results showed that California and Bangkok papaya seed extracts had antioxidant activity with IC50being 24.4 ppm and 22.2 ppm, respectively. Both extracts were also able to inhibit the growth of cancer cells (MCF-7) and did not render any toxic effects on non-cancer cells at low concentrations. The metabolites contained in the two extracts were alkaloid, phenol hydrocarbon, flavonoid, fatty acid, and terpenoid groups. This study showed that papaya seeds have the potential to be further developed in medical field, especially as natural antioxidants and natural cancer-preventing ingredients.